Ethanol-Based Biodiesel from Waste Vegetable Oil - Mary Grace M. Oliveros; Amiliza B. Baiting; ,Menchie G. Lumain; Maria Theresa I. Cabaraban (ASEAN Journal of Chemical Engineering, 2007)
Waste vegetable oil, mainly coming from frying residues, can be used as raw material to obtain a diesel fuel (biodiesel). Biodiesel, a nontoxic, biodegradable, diesel-like fuel, is an important energy alternative capable of decreasing environmental problems caused by the consumption of fossil fuels. The utilization of waste vegetable oils as raw material in biodiesel production was studied. Research was undertaken to establish the availability of used vegetable oil to supply a biodiesel process. It is intended that this work forms an academic study combined with an environmental and technological analysis of the merits of biodiesel as a sustainable fuel. Laboratory experimentation investigated the possibility of using waste vegetable oil from the local fast food chains, and potassium hydroxide as catalyst for the transesterification process. The cleaned waste vegetable oil undergoes transesterification for 4 hours, after which, the biodiesel is separated from the glycerin by gravity. Washing is necessary to remove residual catalyst or soap. Overall material balance for the process gives: 1 kg Waste Vegetable oil + 0.18 kg EtOH + 0.01 kg KOH → 0.74 kg Biodiesel + 0.44 kg Glycerin The biodiesel, in pure form (B100) and in 50% proportion (B50) with petroleum diesel, was run in an essentially unmodified Toyota 2C diesel engine. Smoke density (opacity) and CO exhaust emission both decreased with B50. However, Nox increased with B50. Fuel consumption during engine power testing is significantly greater using the biodiesel, but is also significantly reduced with B50.